A New Species of Mites of the Genus Bdella (Acari, Bdellidae) from Ukraine - Maslov, S.I.; Khaustov, A.A. (Вестник зоологии, 2013)
Bdella kuznetsovi Maslov et Khaustov, sp. n. is described from storm detritus of Black Sea and Sivash Gulf of the Sea of Azov, Ukraine.